Characteristics of Parathyroid Ultrasound in Chronic Kidney Disease Patients Undergoing Hemodialysis - Rosyidi, Muhammad Yunus; Ferriastuti, Widiana; Widodo, Widodo (Transpublika Publisher, 2025)
Research on parathyroid ultrasound in kidney failure patients is highly relevant for understanding the relationship between parathyroid hormone levels and clinical conditions, optimizing therapeutic management for CKD patients. This study employs a quantitative observational descriptive design with cross-sectional approach to provide comprehensive overview of parathyroid ultrasound characteristics in CKD patients. Data were obtained from secondary medical records and parathyroid ultrasound examinations of CKD patients undergoing hemodialysis. This research shows that majority of chronic kidney disease (CKD) patients undergoing hemodialysis at Dr. Soetomo Regional Hospital in Surabaya have elevated serum iPTH and phosphate levels, while calcium levels are generally normal, though some patients experience hypocalcemia. Demographically, majority of patients are women (58%), aged 41–60 years, undergoing hemodialysis for 1–10 years. Parathyroid gland examination through ultrasound shows most patients have hypoechoic echogenicity, oval shape, well-defined borders, solid architecture, and size of 0.51–1 cm. More than half show no detectable vascularization, while some show perilesional blood flow patterns, serving as important indicators for detecting parathyroid hyperplasia. There is correlation between serum iPTH levels and morphological characteristics of parathyroid glands, including echogenicity, shape, size, and vascularization. At iPTH levels <500 pg/dL, parathyroid appears isoechoic to hypoechoic, oval, solid, measuring approximately 0.51–1 cm, with minimal vascularization. At 500–1000 pg/dL, perilesional vascularization begins appearing. When iPTH levels >1000 pg/dL, parathyroid enlarges (>1 cm), becomes hypoechoic in texture, and vascularization increases significantly, indicating more prominent morphological and vascular changes associated with increasing iPTH levels.